ENZYMES IN TECHNOLOGICAL TREATMENT OF WINES ANTIOXIDANT SYSTEM INCLUDED IN OXIDATING PROCESSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The intensity of oxidative enzymatic processes depends on technological methods. At the same time, conditions are created for the passage of secondary redox processes. Knowledge of the chemistry of enzyme preparations will allow you to correctly build a technology for preparing wines depending on their type. Resistance to environmental influences is determined by the state of the antioxidant defense (AD) components. The AZ system includes both the enzyme SOD, catalase, peroxidase and antioxidants represented by glutathione, pigments, phenolic compounds, which are present in wines